2018
DOI: 10.1111/1468-0009.12340
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Parental and Medical Leave Policies on Socioeconomic and Health Outcomes in OECD Countries: A Systematic Review of the Empirical Literature

Abstract: Historically, reforms that have increased the duration of job‐protected paid parental leave have improved women's economic outcomes. By targeting the period around childbirth, access to paid parental leave also appears to reduce rates of infant mortality, with breastfeeding representing one potential mechanism. The provision of more generous paid leave entitlements in countries that offer unpaid or short durations of paid leave could help families strike a balance between the competing demands of earning incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
103
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(115 citation statements)
references
References 137 publications
1
103
0
11
Order By: Relevance
“…Our understanding of the effects of state provision of paid leave relies primarily on data from outside the United States because the United States is the only Organization for Economic Co‐operation and Development (OECD) country without a national paid parental leave policy (although some states have limited paid leave policies). A review of the impact of parental and medical leave policies in OECD countries concluded that paid parental leave improves women's economic outcomes (i.e., increases employment rates, job retention, wages), reduces infant mortality, and helps parents address competing demands of work and family (Nandi et al, ). As paid leave rolls out state by state in the United States, recent studies have captured the effects of this natural experiment on families.…”
Section: Paid Work and Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our understanding of the effects of state provision of paid leave relies primarily on data from outside the United States because the United States is the only Organization for Economic Co‐operation and Development (OECD) country without a national paid parental leave policy (although some states have limited paid leave policies). A review of the impact of parental and medical leave policies in OECD countries concluded that paid parental leave improves women's economic outcomes (i.e., increases employment rates, job retention, wages), reduces infant mortality, and helps parents address competing demands of work and family (Nandi et al, ). As paid leave rolls out state by state in the United States, recent studies have captured the effects of this natural experiment on families.…”
Section: Paid Work and Familiesmentioning
confidence: 99%
“…International research suggests a potential tipping point, where leaves for 6 to 12 months may have negative effects on women's labor force commitment (Gangl & Ziefle, ). Although the benefits of paid leave are positive, studies of unpaid leave, offered through the Family and Medical Leave Act, show it has little effect on women's economic participation (Nandi et al, ). Moreover, Rossin () suggested that unpaid leave may actually increase disparities because it only benefits those mothers who can afford to take it (Milkman & Applebaum, ).…”
Section: Paid Work and Familiesmentioning
confidence: 99%
“…Despite extensive research on preventive and therapeutic interventions, the evidence for informing specific national social policy strategies to lower childhood diarrhoea prevalence through these mechanisms remains limited 4 13 16. Extending the duration of legislated paid maternity leave has been associated with lower infant mortality in a sample of 18 Organisation for Economic Co-operation and Development countries17–20 and a sample of 20 LMICs 21. In addition, more generous paid maternity leave policies were associated with increased breastfeeding practices22–27 and vaccination uptake 28 29.…”
Section: Introductionmentioning
confidence: 99%
“…According to Rostgaard (2002, p. 344), by offering gender equality, paternal leave policies can encourage better relationships between children and fathers; therefore, advancing children's well-being outcomes. Furthermore, father leave policies can help mothers to return to their job and lead them to participate in the labour market; as a result of that, gender inequalities in labour force participation might be lessened (Nandi et al, 2018;Dearing, 2016). Based on Bratberg and Naz's (2014, p. 508) findings, there is also a relationship between fathers' use of paternity leave and the reduced use of mothers' sickness absence, leading to a change in the employers' notions about hiring women.…”
Section: Introductionmentioning
confidence: 99%